Analysis of Social-Emotional Behavior in Students with Autism Spectrum Disorder, ADHD, and Anxiety in Inclusive Schools - Minsih, Minsih; Mujahid, Imam; Uslan, Uslan; Fauzana, Nana; Marpuah, Siti; Helzi, Helzi (Universitas Muhammadiyah Surakarta, 2025)
This research aims to describe the characteristics of children with barriers to social-emotional behavioral in inclusive elementary school. This research uses a qualitative case study design which only examines the characteristics of three children with socio-emotional behavior disorders. The informants are class teachers, guardians of students (teacher Shadow) with Autism Spectrum Disorder (ASD), Attention Deficit and Hyperactivity Disorder (ADHD), and Withdrawal Anxiety Disorder, Parent and Student Regular. Data collection uses interviews, observations, and documentation studies. Data Validation uses Method triangulation dan resource triangulation. Data analysis techniques use content analysis techniques or thematic analysis to identify patterns and themes in interpretive data with reduction, display, and conclusion stages. The results of the study showed that student with ASD and ADHD and Anxiety Disorders have various characteristics that lead to obstacles in social emotional behavior in the form of: stereotypical movements, difficulty focusing, difficulty interacting socially, often rushing, difficulty communicating with people, like to talk to themselves and repeat sentences spoken by the other person, laugh easily and get angry easily for no reason, and dislike crowds. This is based on the results of the identification and assessment carried out by the school inclusion team on children with special needs which include: inclusion coordinators, guardians of students with special needs (teacher shadows), psychologists, occupational therapists, speech therapists and physiotherapists. The implications of this article can be used as a reference and reference in detecting and assessing social emotional behavioral disorders in the development of elementary school-age students.